(untitled) (La Lupa. Colección fueguina de divulgación científica, 2025)
Comité Editorial Editoras responsables Pamela Alli Sabrina Labrone Editores asistentes María Bagur Ana R. Butto Damián A. Fernández Maité Latorre María Paz Martinoli Fernando Santiago Asesores informáticos Enrique Solchman Rodrigo Leandro Gauna Diseño y Diagramación Irina Castro Peña Ushuaia, Tierra del Fuego, Argentina Instagram: @disenioalsur Impresión M&A Diseño y Comunicación S.R.L. Buenos Aires, Argentina E-mail: info@myaweb.com.ar